Factors Influencing Events Dysfunction Cognitive Post Operation on Patient Elderly: Systematic Review - Kusuma, Ratna; Veibiani, Nindita Arum (Indonesian Journal of Medicine, 2025)
Background: : Improvements in global life expectancy have led to a significant increase in the elderly population, which in turn results in a growing number of elderly patients undergoing surgery. This condition raises the risk of postoperative complications, such as postoperative cognitive dysfunction (POCD). POCD can reduce quality of life, prolong the length of hospital stay, and increase mortality. This study aims to identify and synthesize the factors that influence the occurrence of POCD in elderly patients. Subjects and Method: This study is a Systematic review with PICO. The article used in research were obtained from several databased including Google Scolar, Scopus, and PubMed Keywords to find articles are "postoperative cognitive dysfunction," "elderly patients," and "geriatrics". This articles used are failing to directly discuss risk factors for postoperative cognitive dysfunction in elderly patients, or identified as opinion pieces, conference abstracts without full text, or narrative reviews, will be excluded. Articles were selected using PRISMA flow diagram. Results: a total 8 articles reviewed in Systematic Review showed that The incidence of POCD in the elderly shows significant variation between studies, ranging from 8.33% to 37.7% . Risk factors that have been consistently identified as having a significant influence on the incidence of POCD include advancing age, low level of education, number of comorbidities, high ASA score, long duration of anesthesia, intraoperative hypotension, history of cerebral infarction, and low oxygen saturation at induction. The use of certain anesthetic agents such as sevoflurane and midazolam has also been shown to increase the risk of POCD. Instead, use dexmedetomidine preoperative, analgesia preemptive and the combination of general anesthesia with epidural block were identified as protective factors. Conclusion: The main risk factors advanced age, education level, comorbidities, and type and duration of anesthesia.